Malaria in Indonesia: current treatment approaches, future strategies, and potential herbal interventions - Tina Christina L. Tobing; Wahrianto; Eka Saputri; Nasywa Inayah Wafa; Putri Daffa Zulfianti; Lidwina Iswari Sihaloho; Annisa Rabbiatul Husna; Devia Salsabila; Fito Hansen Hotasi Silalahi; Alex Insandus Sitohang; Aysiah Sabrina; Atika Darayani Hasyati Harianja; et al. (Pensoft Publishers, 2024)
Malaria remains a significant public health challenge in Indonesia, with varying prevalence across regions, particularly in eastern provinces like Papua and West Papua. This parasitic disease, transmitted by Plasmodium-infected Anopheles mosquitoes, continues to burden affected populations. Contemporary treatment approaches predominantly rely on Artemisinin-based Combination Therapy (ACT). However, the emergence of drug resistance, coupled with environmental and demographic factors, presents ongoing challenges. This paper explores current malaria treatment strategies in Indonesia, emphasizing the importance of vigilance in the face of drug resistance and the need for innovative approaches. Additionally, it discusses the potential of herbal interventions, drawing from the rich traditional knowledge of medicinal plants in Indonesia. Secondary metabolites found in herbs, including flavonoids, terpenoids, and alkaloids, show promise as antimalarial agents. As Indonesia and the global community strive to combat malaria, research, surveillance, and healthcare infrastructure development must remain at the forefront of strategies. Despite the complex nature of malaria control, continued dedication and collaboration offer hope for reducing the disease's impact and progressing towards its eventual elimination. Graphical abstract: